EKSTRAK DAUN KATUK (Sauropus androgynus (L) Merr) SEBAGAI ANTIBAKTERI TERHADAP Propionibacterium acnes dan Staphylococcus epidermidis - Yuli Wahyu Tri Mulyani; Dadan Hidayat; Isbiyantoro Isbiantoro; Yeni Fatimah (JFL : Jurnal Farmasi Lampung, 2017)
Katuk is one of the most common plant species in Indonesia which is known by the community to treat the disease, especially the leaf part can be used as a milk mat. katuk leaf (Sauropus androgynus (L) Merr) also contains saponin, flavonoid and tannin Inhibits the growth of bacteria one of the bacteria that cause acne bacteria P. acnes and S. epidermidis. The aim of this research is to know the antibacterial inhibition effect of katuk leaf extract to growth of P. acnes and S. epidermidis using Cup-plate or pit diffusion method with concentration 20%, 40%, 60%, 80% and 100%. Clindamycin is used as a positive control and aquades as a negative control. The leaves of katuk extracted with 70% ethanol solvent showed no antibacterial activity against P. acnes bacteria while against S. epidermidis bacteria showed antibacterial activity. The highest antibacterial activity at 100% concentration with 18.17 mm zone diameter belong to the category of inhibitory resistance of medium growth and the lowest concentration at concentration of 40% with 16.68 mm inhibitory zone diameter belong to the weak growth inhibitory response category. The minimum inhibitory concentrations produced in S. epidermidis bacteria were 39% - 36%. Keywords : Sauropus androgynus, Propionibacterium acnes, Staphilococcus epidermidis, Minimal Inhibitory Concentration.